Marketing Channel Analysis of Robusta and Arabica Coffee in Gandang Batu Sillanan District Tana Toraja Regency - Wasti Wasti; Bahari Bahari; Surni Surni (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This research was motivated by the advantages, margins and efficiency of robusta and arabica coffee marketing in Gandang Batu Sillanan District, Tana Toraja Regency. This research aims(1) knowing the marketing channels of robusta and arabica coffee in gandang batu sillanan district of tana toraja regency (2) knowing the benefits and marketing margins of robusta and arabica coffee in gandang batu sillanan district of tana toraja regency and (3) Knowing the level of marketing efficiency and total efficacy of robusta and arabica coffee in gandang batu sillanan district of tana toraja regency.The study was analyzed using descriptive, margin and farmer's share analysis. The population and samples in the study used the purposive sampling method, which is a deliberate sampling technique using the criteria that coffee farmers' main livelihoods as coffee farmers, the determination of merchant respondents was determined using the snowball sampling method. This research obtained the following results; (1)marketing channels from farmers to consumers, namely;(a)Farmers sell to wholesalers then sell to consumers(b)Farmers sell to collecting merchants then sold to wholesalers and then sell them to consumers (2)On channel I wholesalers get a profit of IDR 11,795/kgand a margin of IDR12,000/kg while channel II collecting merchants get a profit of IDR4,639/kg and a margin of IDR5,000/kg while wholesalers get IDR 11,795/kg and margins of IDR 12,000/kg. (3)Percentage of the price share received by the manufacturer on channel I is 59% and channel II is 64%. The total number of large traders on channel I is IDR 12,974,500, while in channel II the total profit of collecting traders amounted to IDR 4,764,840 and wholesalers of IDR 4,175,100.